Therapeutic index of lymphadenectomy among patients with pancreatic neuroendocrine tumors: A multi‐institutional analysis. Issue 7 (29th August 2019) - Wu, Lu; Sahara, Kota; Tsilimigras, Diamantis I.; Maithel, Shishir K.; Poultsides, George A.; Rocha, Flavio G.; Weber, Sharon M.; Fields, Ryan C.; Idrees, Kamran; Cho, Clifford S.; Shen, Feng; Pawlik, Timothy M.; et al.
Abstract: Background: The benefit derived from lymph node dissection (LND) in patients with pancreatic neuroendocrine tumors (pNETs) based on clinicopathological characteristics remains unclear. Methods: Patients undergoing surgery for pNET between 1997 and 2016 were identified using a multi‐institutional dataset. The therapeutic index of LND relative to patient characteristics was calculated. Results: Among 647 patients, the median number of lymph nodes (LNs) evaluated was 10 (interquartile range: 4‐16) and approximately one quarter of patients had lymph node metastasis (LNM) (N = 159, 24.6%). Among patients with LNM, 5‐year recurrence‐free survival was 56.0%, reflecting a therapeutic index value of 13.8. The therapeutic index was highest among patients with a moderately/poorly‐differentiated pNET (21.5), Ki‐67 ≥ 3% (20.1), tumor size ≥2.0 cm (20.0), and tumor location at the head of the pancreas (20.0). Patients with ≥8 LNs evaluated had a higher therapeutic index than patients who had 1 to 7 LNs evaluated (≥8: 17.9 vs 1‐7: 7.5; difference of index: 11.4). Conclusion: LND was mostly beneficial among patients with pNETs >2 cm, Ki‐67 ≥ 3%, and lesions located at the pancreatic head as identification of LNM was most common among individuals with these tumor characteristics. Evaluation of ≥8 LNs was associated with a higher likelihood of identifying LNM as well as a higher therapeutic index, and therefore this number of LNs should be considered the goal.